High performance Al-air batteries (AABs) with reduced corrosion - Chen, Juntong (Nanyang Technological University, 2022)
Al-air batteries are candidates for next-generation energy storage devices due to advantages including theoretical high energy density, low cost, eco-friendliness, etc. However, the self-corrosion reaction of the Al anode in the alkaline electrolyte is a fatal drawback that prevents the practical usage of Al-air batteries.